Comparison of psychopathological dimensions between major depressive disorder and schizophrenia spectrum disorders focusing on language, affectivity and motor behavior. (April 2017) - Steinau, Sarah; Stegmayer, Katharina; Lang, Fabian U.; Jäger, Markus; Strik, Werner; Walther, Sebastian
Abstract: This study tested whether patients with major depressive disorder (MDD) and schizophrenia spectrum disorders would differ in three dimensions of psychopathology (language, affectivity and motor behavior) as assessed by the Bern Psychopathology Scale (BPS) in a cohort of 58 patients with MDD and 146 patients with schizophrenia spectrum disorders. The overall estimation of severity of each of the three dimensions was rated on a seven-point Likert scale from severely inhibited to severely disinhibited. Here, more than half of the patients endorsed ratings that showed normal or mildly (dis-)inhibited behavior. At group level more pronounced negative ratings of affect were seen in MDD. Group comparisons of the severity ratings on language or motor behavior yielded no differences between schizophrenia spectrum disorders and MDD. At the individuals' levels, extreme ratings in the language and motor dimensions were more frequent in schizophrenia spectrum disorders and in the affectivity dimension more frequent in MDD. Shared psychopathological features could be seen across diagnoses, supporting a dimensional approach to psychopathology in endogenous psychoses. However, the groups differ in the severity of affect ratings as well as in the distribution of language, affectivity and motor ratings with more variance among the group of schizophrenia spectrum disorders. Highlights: Assessment of psychosis symptom dimensions in schizophrenia and major depression. increased negative affect ratings in MDD, but similar language and motor behavior. extreme ratings of motor and language dimensions more common among schizophrenia. psychosis dimensions support transdiagnostic assessment in MDD and schizophrenia.